MEREGUK KENIKMATAN DI DUNIA MAYA: VIRTUALITAS DAN PENUBUHAN DALAM CYBERSEX - Budi Irawanto (Jurnal Kawistara, 2017)
Dubbed methaporically as “sex without secretions”, cybersex has transformed the sexual practice and the meaning of erotica. This article seeks to explore the issues of sexuality in cyberspace, particularly its virtuality and embodiment in cybersex.  Many discussions on cybersex revolve around issues of accessibility, affordability and anonymity that draw sharp lines between the real and the virtual. Therefore, in this article I argue that cybersex does not completely distinct from sexuality in the real world due to the interpenetration process between sex in the virtual and real world.